2020
DOI: 10.1073/pnas.2016112117
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of muscle-derived exosomal miRNAs induced by HIIT improves insulin sensitivity through down-regulation of hepatic FoxO1 in mice

Abstract: Implementation of regular physical activity helps in the maintenance of a healthy metabolic profile both in humans and mice through molecular mechanisms not yet completely defined. Here, we show that high-intensity interval training (HIIT) modifies the microRNA (miRNA) profile of circulating exosomes in mice, including significant increases inmiR-133aandmiR-133b. Importantly, treatment of sedentary mice with exosomes isolated from the plasma of trained mice improves glucose tolerance, insulin sensitivity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 56 publications
2
86
2
4
Order By: Relevance
“…The top two most significantly enriched biological processes revealed by gene ontology analysis were the response to reactive oxygen species and insulin secretion. This is in line with a recent study in mice showing that miRNA-containing EVs isolated from high-intensity interval-trained muscles improved glucose tolerance when administered to sedentary mice ( Castaño et al, 2020 ). However, due to the inability to label and track EVs released from specific cells or tissues, the relative contribution of skeletal muscle to circulating EVs induced by exercise is still mostly speculative ( Nederveen et al, 2020 ).…”
Section: Micrornas and Extracellular Vesiclessupporting
confidence: 91%
“…The top two most significantly enriched biological processes revealed by gene ontology analysis were the response to reactive oxygen species and insulin secretion. This is in line with a recent study in mice showing that miRNA-containing EVs isolated from high-intensity interval-trained muscles improved glucose tolerance when administered to sedentary mice ( Castaño et al, 2020 ). However, due to the inability to label and track EVs released from specific cells or tissues, the relative contribution of skeletal muscle to circulating EVs induced by exercise is still mostly speculative ( Nederveen et al, 2020 ).…”
Section: Micrornas and Extracellular Vesiclessupporting
confidence: 91%
“…STAT3 induces the expression of Fbxo40, a muscle-specific E3 ubiquitin ligase that stimulates ubiquitin conjugation, leading to degradation of IRS1 [11,48,76]. Some authors such as Castaño et al or Barlow et al have described that exercise could change the expression of these miRNAs, improving insulin sensitivity [69,77]. Consequently, the knowledge of exosomes and their targets could serve as a potential therapy in metabolic syndrome.…”
Section: Muscle Exosomal Mirnasmentioning
confidence: 99%
“…The injection of EVs produced by adipose tissue-derived macrophages were found to modulate insulin resistance depending on the donor mice; EVs from lean mice attenuated insulin resistance in obese mice, while EVs from obese mice caused insulin resistance in recipient lean mice [ 165 ]. Similarly, the administration of plasma EVs from high-intensity interval-trained mice improved glucose tolerance and insulin sensitivity in sedentary animals [ 166 ] and, notably, in both studies, the effect was found to be mediated, at least in part, by miRNAs transferred by EVs. The potential applications of EVs are also being investigated with regard to other pathologies and complications.…”
Section: Potential Applications Of Extracellular Vesicles Introduced In Circulationmentioning
confidence: 99%